A Historical Perspective of Medical Education - Huseyin Balcioglu; Ugur Bilge; Ilhami Unluoglu (Journal of Education in Science, Environment and Health)
Even though there are significant developments in recent years in medical education, physicians are still needed reform and innovation in order to prepare the information society. The spots in the forefront of medical education in recent years; holistic approach in all processes, including health education, evidence-based medicine and professionalism. Medical education; undergraduate, postgraduate and continuing medical education covering the period varies from country to country for the duration of this period. Increasing day pursuing the importance of medical education and student-centered education and is spread across the country as well as in blended learning model that includes educational centered education. Medical faculty, students and teaching staff should be informed about innovations and developments should offer opportunities for that matter, should support administrative and economic necessarily.